Ozonation Pretreatment Evaluation for Xylanase Crude Extract Production from Corncob under Solid-State Fermentation - Efri Mardawati; Surya Martha Pratiwi; Robi Andoyo; Tita Rialita; Mochamad Djali; Yana Cahyana; Een Sukarminah; In-In Hanidah; Imas Siti Setiasih (Universitas Padjadjaran, 2017)
Xylanases are highly exploited enzyme in industries, including food and chemical industry. Xylanases can be utilized in catalyzing the endohydrolysis of 1,4-β-xylosidic linkages in xylan, lignocellulosic component to produce xylose-monomer. This research aims to optimize xylanase production from alternative substrate, corncob. Corncob contains 41.17% of hemicellulose, polymer of xylan. Xylanases are produced through solid state fermentation by Trichoderma viride. Ratio between substrate and moistening solution was 0.63 g/mL with fermentation temperature 32,8OC. Variables varied include incubation time and pretreatment (using autoclave, ozonation, combination of ozonation and autoclave, also without pretreatment). Xylanase activity was measured by DNS method using 1% of xylan as substrate standard. The result showed that the best incubation time is 36 h with 14403.8707 U/mg protein for specific xylanase activity by using autoclave as pretreatment. Ozonation pretreatment process can increase the enzyme activity of xylanase.